Department Budgeting and Resources - Don Chu (Academic Chairpersons Conference Proceedings, 2018)
Since the Great Recession, department chairs have faced reduced appropriations and increased demands on their budgets. Public appropriations have declined, students have been squeezed by tuition and fee increases, and department resources are stretched thin. Making matters more problematic is the fixed nature of most budget allocations, leaving chairs with precious little funding available for investment in the department’s future. What can chairs do to respond to this fiscal environment and to position their departments for a brighter future? In this interactive session, we will look at the three keys to managing the budget and increasing resources for your department. First, chairs need to understand their budgets and how budgets are constructed. Next, chairs can manage their budgets, increase department productivity and work with their deans to invest resources in the department. Lastly, chairs can take steps to increase resource flow into their department.
Keywords: Department Budgeting Resources Operating Finances Chair